Teaching Participative Justice in Professional Writing. Issue 2 (3rd April 2022) - Hashlamon, Yanar; Teston, Christa
ABSTRACT: Technical and professional communication (TPC) curricula tend to prioritize hyperpragmatist learning outcomes, objectives, and activities. Drawing on a grounded theory analysis of curricular self-assessment data, including interviews with community partners, we argue that TPC in the U.S. is at constant risk of co-option by market logics. Through a speculative curricular framework that works toward building more just, liveable worlds, this essay reimagines TPC curricula as an opportunity to redress inequities caused by exploitative market logics.